Tax-Motivated Trading and Price Pressure: An Analysis of Mutual Fund Holdings - Gibson, Scott; Safieddine, Assem; Titman, Sheridan (Journal of Financial and Quantitative Analysis, 2000)
Scott Gibson, Assem Safieddine, Sheridan Titman, Tax-Motivated Trading and Price Pressure: An Analysis of Mutual Fund Holdings, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 3 (Sep., 2000), pp. 369-386